South Africa's Developing Deterrence Regime: how the Retraction of Employment and Political Rights of Refugees and Asylum Seekers Poses a Threat to the Principle of Non-Refoulement - Kruger, Sky (Department of Public Law, 2025)
Recent amendments to South Africa's domestic refugee law, the Refugees Act 130 of 1998, have seen a number of restrictions to asylum policy. The 2017 amendments in tandem with the 2020 regulations have retracted the automatic right to work for asylum seekers as well as placed a prohibition on political activity for refugees and asylum seekers. These amendments make it incredibly difficult, if not impossible, for asylum seekers to sustain themselves during their sojourn and increase the likelihood of enforced destitution. The amendments further prohibit the political activity of refugees and asylum seekers within South Africa as well as in relation to their country of origin. These amendments, this dissertation argues, fit within a broader move towards a more restrictive asylum policy within South Africa based on the idea of deterrence. South Africa's anti-migrant and anti-refuge sentiment are creating a regime built on deterrence in order to reduce the numbers of current and prospective refugees and asylum seekers. One such method of deterrence that this dissertation focuses on is the retraction of vital socioeconomic and political rights that exacerbate the plight of refugees and asylum seekers. The existing framework that frustrates the ability to work for refugees as well as the administrative and adjudicative backlogs and xenophobia are assessed as manifestations of South Africa's desire to render its asylum system inaccessible. Further, the retraction of employment rights and the prohibition on political activity pose a fundamental risk to the cardinal principle of refugee law, non-refoulement. Enforced destitution as a result of the inability to sustain oneself as well as the suppression of political autonomy are likely to create conditions of sojourn that are so unbearable that refugees and asylum seekers may have no choice but to return to a country where they face a wellfounded fear of persecution or serious harm. This dissertation thus explores the notion of constructive refoulement as a serious potential consequence of the restriction of the rights of refugees and asylum seekers. By making conditions so unbearable that refugees and asylum seekers may have no choice but to leave or may be dissuaded from seeking asylum in South Africa, the government is moving towards a deterrence regime. This is not unique to South Africa as it is argued that this is a trend observed globally, particularly in the Global North where States go to great lengths to restrict access to their asylum system and deter forced migrants. Through assessing similar restrictive policies that manifest in the Global North and exploring how South Africa has actively sought to adopt restrictive immigration policies from the Global North, it is argued that South Africa is recreating the Global North's anti-refugee environment. This anti-refugee environment is justified under the supposed threat that migrants and refugees represent. This threat is more a social construction than an objective reality. Thus, the notion of securitization is explored as States' justification for its deterrence policies both at the domestic and international level.